2013
DOI: 10.1590/s0036-46652013000200012
|View full text |Cite
|
Sign up to set email alerts
|

THE FIRST CASE OF Angiostrongylus cantonensis EOSINOPHILIC MENINGITIS DIAGNOSED IN THE CITY OF SÃO PAULO, BRAZIL

Abstract: SUMMARYIntroduction: Angiostrongylus cantonensis is a natural parasite found in lung arteries of rats, which in humans may cause eosinophilic meningitis. Objective: To report the first case of eosinophilic meningitis caused by Angiostrongylus cantonensis in the city of São Paulo, Brazil. Case report: A male patient, 11 years old, living in the southern area of São Paulo, was admitted to the Pediatric Emergency Department with ongoing headaches for three days, but no fever or any other complaint. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…All human cases of H. gingivalis infections reported to date were diagnosed at autopsy, despite antemortem suspicions of parasitic infection in some cases. Neurological nematodiasis is rare but can involve parasites such as Angiostrongylus cantonensis, Strongyloides stercoralis, Toxocara canis, Trichinella spiralis, and Gnathostoma spinigerum, typically associated with CSF and peripheral eosinophilia (39)(40)(41)(42)(43)(44)(45)(46). During H. gingivalis infection, CSF may initially show only moderate pleocytosis and eosinophilia may be absent (10,11) and larvae are usually not found in CSF obtained by lumbar puncture.…”
Section: Case Reportmentioning
confidence: 99%
“…All human cases of H. gingivalis infections reported to date were diagnosed at autopsy, despite antemortem suspicions of parasitic infection in some cases. Neurological nematodiasis is rare but can involve parasites such as Angiostrongylus cantonensis, Strongyloides stercoralis, Toxocara canis, Trichinella spiralis, and Gnathostoma spinigerum, typically associated with CSF and peripheral eosinophilia (39)(40)(41)(42)(43)(44)(45)(46). During H. gingivalis infection, CSF may initially show only moderate pleocytosis and eosinophilia may be absent (10,11) and larvae are usually not found in CSF obtained by lumbar puncture.…”
Section: Case Reportmentioning
confidence: 99%
“…These data are especially useful and can be used by public health authorities to establish policies related to surveillance and planning of preventive actions. Isolated cases of eosinophilic meningoencephalitis have recently been reported in Brazil 9,11,14,15,46,47 . Thus, it is plausible that A. cantonensis continues to spread to new regions, increasing the risk of eosinophilic meningoencephalitis in humans.…”
Section: Several Snails Play Roles As Intermediate Hosts Formentioning
confidence: 99%
“…A. cantonensis has been observed in several regions of the world [3][4][5][6][7] , and they were distributed from Eastern Asia to other continents by two main hosts: rats (definitive hosts) and Achatina fulica Bowdich, 1822 (one of the intermediate hosts), especially during the Second World War 8 . Several species of land and freshwater snails have also been found to be naturally infected with A. cantonensis [9][10][11][12][13][14] . In Brazil, the occurrence of A. cantonensis has been reported in all states except for Acre [9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this scenario began to change with the first reported occurrence in the Americas in 1981 when infected rats and snails were found in Cuba (Aguiar et al 1981). Since that time, the occurrence of A. cantonensis has been reported in the United States of America, Jamaica and Ecuador (Kim et al 2002, Slom et al 2002, Wang et al 2008, Pincay et al 2009); it has recently been found in Brazil (Caldeira et al 2007, Lima et al 2009, Espírito-Santo et al 2013). …”
mentioning
confidence: 97%